Comparative Study of Various Adjustable Speed Drives During Voltage Sag - Renukadevi S; Rathinakumar M (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This Paper compares the sensitivity of various adjustable speed drives to voltage sag for the process control applications. Three phase voltage sag of type B caused due to SLG fault is considered and four topologies of ASD’s are compared in this paper. The comparison is done especially in speed, voltage, current and torque of the ASDs. Diode rectifier without z source inverter, diode rectifier with z source inverter , single phase two leg Vienna rectifier and single phase neutral linked Vienna with z source inverter are compared and the best one is highlighted. The circuits of various ASD’s are simulated using   Matlab /Simulink.